Degradação de silagens de capim-elefante contendo subproduto do urucum - do Rego, Anibal Coutinho [UNESP]; Duarte Candido, Magno Jose; Pereira, Elzania Sales; Feitosa, Jose Valmir; Teles Rego, Margareth Maria (Univ Federal Ceara, Dept Geol, 2010)
To evaluate the dry matter, neutral detergent fiber and crude protein in situ degradation of elephant grass silages with five levels (0; 4; 8; 12 and 16%, on a fresh matter basis) of annatto grain by-product (AGBP), this work was carried out. A split-plot design, consisting on the addition levels the plots and the incubation times the sub-plots, with four replicates, was adopted. For the silages making, the elephant grass was cut 70 days-old and mixed to the by-product, in 20 plastic drums. The samples were dried, grid in a bolter of 5 mm mesh, being used 3 g of samples in each nylon bag, for incubation in the rumem for 0; 6; 48 e 96 hours; 2 ram without defined breed were used. Was observed increased the disappearance of the DM until the level 13.37% of addition of (AGBP) the elephant grass silages for the incubation time 48 hours, this level was that presented the most disappearance DM. For the NDF the disappearance increased until 16% of addition. For the whole of parameters of degradation, was observed that the level of addition of 16% of (AGBP) presented the most values for the potential and effective degradability of variables in question. The inclusion of the annatto grain by-product for elephant grass silage results in greater potential and effective degradability.
Degradation of elephant grass silages with annatto by-product
Keywords: Bixa orellana L.; Degradability; Ensiling; Sheep; Pennisetum purpureum Schum